336 Is a vaginectomy enough or is a pelvic exenteration always required for surgical treatment of recurrent cervical cancer?. (13th November 2020) - Vizzielli, G; Lucia, T; Conte, C; Chiantera, V; Gallotta, V; Foschi, N; Arcieri, M; Ferrandina, G; Fagotti, A; Zattoni, F; Scambia, G; Ercoli, A
Abstract : Introduction: No consensus has yet been reached on the best strategy for treatment of cervical cancer local recurrence. Vaginectomy could be a salvage treatment in selected patients. Methods: The records of vaginal recurrent cervical cancer patients admitted at Fondazione Policlinico 'Agostino Gemelli' IRCCS in Rome from January 2010 to June 2019 were retrospectively analyzed. We reported perioperative and survival outcomes of vaginectomy with respect to a matched series of pelvic exenteration (PE). Results: Fifteen women underwent vaginectomy and 30 patients were submitted to PE. No statistical differences were observed between the two groups at baseline characteristics. The vaginectomy procedures were successfully performed in all women, and no case required conversion to PE. Moreover, a higher rate of major postoperative complications after PE with respect to vaginectomy (p=0.027) were recorded: among them, 3 women required a reoperation within 30 postoperative days, and 4 experienced two or more complications. Twenty-five (55.6%) women experienced recurrence: 8/25 (32.0%) in the vaginectomy group, and 17/25 (68%) in the PE group, with a median progression-free survival of 20 months and 13 months, respectively (p=0.169). In total, 5/15 (33.3%) died of disease in the vaginectomy group and 13/30 (43.3%) in the PE group, with a median overall survival of 39 and 18 months for vaginectomy and PE, respectively (p=0.161). Conclusions: The vaginectomy seems to allow for salvage treatment, like radiotherapy and/or PE, but with a minimal impact on quality of life in appropriately selected women with local recurrent cervical cancer.